Peran Self-Efficacy dan Motivasi terhadap Hasil Belajar: Analisis Perspektif Hadits - Armiya Sayidatun Nafi'ah; Zulkipli Lessy (Al-Kindi, 2026)
This study aims to examine the role of self efficacy and learning motivation on learning outcomes from a hadith perspective. The study employed a qualitative approach with a literature review, focused on the systematic review and analysis of sources in the form of scientific journal articles and relevant hadith books. Data were collected through documentation techniques and analyzed using content analysis to identify the relationship between the concepts of self efficacy, learning motivation, and learning outcomes in modern education, as well as the values contained in the hadith of the Prophet Muhammad (peace be upon him). The results indicate that self efficacy and learning motivation are internal factors that play a significant role in improving student learning outcomes. Self efficacy fosters self confidence, perseverance, and the ability to overcome learning difficulties, while learning motivation serves as the primary driver that maintains the continuity of the learning process. From a hadith perspective, both concepts are grounded in spiritual values such as sound intention, sincerity, and consistency in pursuing knowledge. The integration of scientific findings with the values of hadith demonstrates that learning outcomes are not only academic but also spiritually meaningful, making it crucial to develop them within a holistic educational approach.